2022
DOI: 10.3389/fped.2022.941785
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Aerosols in SARS-CoV-2 Polymerase Chain Reaction-Positive Children and Age-Matched-Negative Controls

Abstract: BackgroundChildren and adolescents seem to be less affected by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease in terms of severity, especially until the increasing spread of the omicron variant in December 2021. Anatomical structures and lower number of exhaled aerosols may in part explain this phenomenon. In a cohort of healthy and SARS-CoV-2 infected children, we compared exhaled particle counts to gain further insights about the spreading of SARS-CoV-2.Materials and MethodsIn this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
1
Order By: Relevance
“…Children also have a lower respiratory minute Additionally, no infected children were found to breathe more than 595 p/L, whereas so-called superspreaders in studies among adults exhaled >5,000 particles/liter and accounted for 15.6% of infected adults (39). At first glance, our aerosol measurements do not match the data from Gutmann et al (48). This study reported significantly increased exhaled aerosol levels in SARS-CoV-2 PCR-positive children and adolescents (median 355.0 p/L) compared to SARS-CoV-2 PCR-negative participants (median 195.0 p/L; p < 0.001).…”
Section: Discussioncontrasting
confidence: 93%
“…Children also have a lower respiratory minute Additionally, no infected children were found to breathe more than 595 p/L, whereas so-called superspreaders in studies among adults exhaled >5,000 particles/liter and accounted for 15.6% of infected adults (39). At first glance, our aerosol measurements do not match the data from Gutmann et al (48). This study reported significantly increased exhaled aerosol levels in SARS-CoV-2 PCR-positive children and adolescents (median 355.0 p/L) compared to SARS-CoV-2 PCR-negative participants (median 195.0 p/L; p < 0.001).…”
Section: Discussioncontrasting
confidence: 93%